Identification of fish spermatogenic cells through high-throughput immunofluorescence against testis with an antibody set - Ye, Ding; Liu, Tao; Li, Yongming; Wang, Yaping; Hu, Wei; Zhu, Zuoyan; Sun, Yonghua (Frontiers in Endocrinology, 2023)
Image-based identification and quantification of different types of spermatogenic cells is of great importance, not only for reproductive studies but also for genetic breeding. Here, we have developed antibodies against spermatogenesis-related proteins in zebrafish (Danio rerio), including Ddx4, Piwil1, Sycp3, and Pcna, and a high-throughput method for immunofluorescence analysis of zebrafish testicular sections. By immunofluorescence analysis of zebrafish testes, our results demonstrate that the expression of Ddx4 decreases progressively during spermatogenesis, Piwil1 is strongly expressed in type A spermatogonia and moderately expressed in type B spermatogonia, and Sycp3 has distinct expression patterns in different subtypes of spermatocytes. Additionally, we observed polar expression of Sycp3 and Pcna in primary spermatocytes at the leptotene stage. By a triple staining of Ddx4, Sycp3, and Pcna, different types/subtypes of spermatogenic cells were easily characterized. We further demonstrated the practicality of our antibodies in other fish species, including Chinese rare minnow (Gobiocypris rarus), common carp (Cyprinus carpio), blunt snout bream (Megalobrama amblycephala), rice field eel (Monopterus albus) and grass carp (Ctenopharyngodon idella). Finally, we proposed an integrated criterion for identifying different types/subtypes of spermatogenic cells in zebrafish and other fishes using this high-throughput immunofluorescence approach based on these antibodies. Therefore, our study provides a simple, practical, and efficient tool for the study of spermatogenesis in fish species.